Sartre’s Existentialism for Grant and Jefferson’s Educational Commitment in Ernest J. Gaines’s Novel: A Lesson Before Dying - Rina Wahyu Setyaningrum; Fabiola Dharmawanti Kurnia; Ali Mustofa (Vivid: Journal of Language and Literature, 2020)
Racism and Injustice have put Jefferson, a poor young black man, into an electrocution for murder and burglary that he has never done. As a coloured, he cannot do anything than accept the defense attorney verdict – white American Supreme Court’s desegregation – who addresses him as a “hog.” It leaves an inferior feeling that he is nothing but a hog.  Comparing him to a hog attracts Miss Emma’s protest that she would like him walking to the electric chair as a human. Therefore, to get Jefferson understands that he is worth a man, she asks Grant Wiggins – an educated black teacher to educate him so he could die a man. In fact, the biggest challenge Grant faces when he looks at Jefferson is his feeling of looking at himself as a man experiencing the same type of racism and discrimination at the oppressive white community. Whereas, educating Jefferson to be a man is difficult as he has to make himself confident with his existence before determining ways of assuring Jefferson as an existing man who will walk to the electric chair on two feet, not a hog. Educating is underpinning people to have great control over lives and surroundings. Its importance deals with functioning the knowledge significant to empower. This is convincing that Jefferson should be educated so that he will not degrade himself as coloured because of his inability to say even a word to defend himself. Using the existentialism philosophy, Grant and Jefferson’s educational commitment in A Lesson Before Dying is discussed based on five themes of Sartre’s existentialism. It reveals that Grant does not get any positive response once he starts teaching. Gradually, Jefferson speaks to him after being attracted by his personal feelings. Grant’s ultimate achievement is when he can make Jefferson writes a diary, to portray some individual matters. What Grant has accomplished is his ability to link the themes, relevant to the philosophy of education. Grant succeeds in transforming Jefferson as a man who has dignity.